Robotic mitral valve surgery - John Massey; Kenneth Palmer; Omar Al-Rawi; Owen Chambers; Tim Ridgway; Selvaraj Shanmuganathan; Gopal Soppa; Paul Modi (Frontiers in Cardiovascular Medicine, 2024)
Totally endoscopic robotic mitral valve repair is the least invasive surgical therapy for mitral valve disease. Robotic mitral valve surgery demonstrates faster recovery with shorter hospital stays, less morbidity, and equivalent mortality and mid-term durability compared to sternotomy. In this review, we will explore the advantages and disadvantages of robotic mitral valve surgery and consider important technical details of both operative set-up and mitral valve repair techniques. The number of robotic cardiac surgical procedures being performed globally is expected to continue to rise as experience grows with robotic techniques and increasing numbers of cardiac surgeons become proficient with this innovative technology. This will be facilitated by the introduction of newer robotic systems and increasing patient demand.